2022
DOI: 10.1128/aem.02378-21
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the GATA-Type Transcription Factor PaNsdD in the Filamentous Fungus Podospora anserina and Its Interplay with the Sterigmatocystin Pathway

Abstract: The model ascomycete Podospora anserina , featured by its strict sexual development, is a prolific but yet unexploited reservoir of natural products. The GATA-type transcription factor NsdD has been characterized by the role in balancing asexual and sexual reproduction, and governing secondary metabolism in filamentous fungi. In the present study, we functionally investigated the NsdD ortholog PaNsdD in P. anserina . Compared to the wild-type strain, vegetative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In recent years, with the continuous improvement of genome databases, more and more TF families have been identified, such as bZIP [ 22 ], MYB [ 23 ], GATA [ 24 ], and PacC [ 25 ]. bZIP TFs are one of the most widely distributed and conserved proteins of eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the continuous improvement of genome databases, more and more TF families have been identified, such as bZIP [ 22 ], MYB [ 23 ], GATA [ 24 ], and PacC [ 25 ]. bZIP TFs are one of the most widely distributed and conserved proteins of eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…To counteract this thorny problem, some smart strategies have been developed in the past decade, based on targeted or global approaches. In previous work, we showed that targeted modification techniques could lead to the functional characterization of ST, a predominant metabolite in the filamentous fungal model P. anserina in liquid culture [ 50 , 51 ], but such an approach obviously limits access to larger metabolite exploitation. In this work, our main objective was to compare the global strategies usually used to deregulate SM gene clusters and illustrate the importance of complementary strategies as a foundation to activate silent BGCs and discover specific products of interest in the model fungus P. anserina .…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, the metabolome diversity of this fungi is underexplored. A few sets of secondary metabolites have been isolated including anserinones A and B, two benzoquinones exhibiting antifungal, antibacterial, and cytotoxic activities [ 48 ], and sterigmatocystin (ST), a polyketide demonstrating larvicidal and antifungal activities [ 49 , 50 , 51 ]. To the best of our knowledge, apart from the ST gene cluster that has been experimentally confirmed and functionally characterized in P. anserina , only seven putative BGCs displaying lower sequence similarity might be assigned to known molecules, while none of the other clusters can be correlated to natural products [ 44 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vvd ( Pa_4_6960 ) gene sequence was identified by searching in the P. anserina genome database, using the N. crassa protein VVD (NCU03967) as a query (Espagne et al ., 2008). The Δ vvd mutant was constructed as previously described (Xie et al ., 2014; Shen et al ., 2022). In brief, a nourseothricin resistance cassette was used as the selection marker, which was amplified using primers 2F/3R from pBC‐nourseo plasmid.…”
Section: Methodsmentioning
confidence: 99%